Late effects of single and repeated sublethal gamma radiations on haemopoietic stem cells in mice - Vávrová, J; Petýrek, P (Folia biologica, 1986)
The effects of single (1 X 5 Gy) and repeated (4 X 5 Gy) gamma-ray doses, separated by 21 days, on femoral CFU-S numbers in mice during the 12 months after irradiation were compared. Nucleated cell and CFU-S numbers were recovered 21 days after whole-body irradiation with 5 Gy. Marrow regeneration was not sufficient after the second irradiation, and nucleated cell and CFU-S numbers reached 50% of the level of the control 21 days after the second dose. The decrease in CFU-S numbers was more marked after the third and fourth doses, reaching 35% of the control. While CFU-S numbers were recovered by the 21st day after a single dose of 5 Gy, the level of the control group was reached 60 days after the last dose of repeated (4 X 5 Gy) gamma irradiation. A decrease in femoral CFU-S numbers occurred in both irradiated groups 6 months after the last dose, the decrease having been more marked in the group exposed to repeated irradiations. The decrease was more pronounced 12 months after irradiation although bone marrow cellularity was at the level of the unirradiated group. Femoral CFU-S numbers were lower in unirradiated 480-day-old mice than in those at 120 days of age.
Keywords: záření gama; buněčné dělení; Animals; Gamma Rays; Female; Age Factors; ženské pohlaví; Hematopoietic Stem Cells; Time Factors; časové faktory; věkové faktory; Mice; myši; Mice, Inbred CBA; myši inbrední C57BL; hematopoetické kmenové buňky; zvířata; myši inbrední CBA; Mice, Inbred C57BL; Cell Division; vztah dávky záření a odpovědi; Dose-Response Relationship, Radiation